1954
DOI: 10.1021/j150511a023
|View full text |Cite
|
Sign up to set email alerts
|

Heats of Adsorption of Argon

Abstract: The calorimetric heats of adsorption have been measured for argon at -195°on a series of carbon blacks graphitized at the successively higher temperatures, 1000, 1500, 2000 and 2700 °. X-Ray and electron microscope studies reported by Schaeffer, et al., indicate a higher degree of graphitization with increasing temperature of heat treatment; this w-ould result in progressively more homogeneous surfaces within the series. Our experimental results illustrate clearly the change in the shape of the heat-coverage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1955
1955
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(32 citation statements)
references
References 1 publication
1
31
0
Order By: Relevance
“…Experimental isosteric heats of argon on GTCB at 77 K are available in the literature, for example, Beebe et al [20,21], Grillet et al [18]. Bobka et al [22], Pace and Siebert [23], and Avgul and Kiselev [19].…”
Section: Isosteric Heatmentioning
confidence: 99%
“…Experimental isosteric heats of argon on GTCB at 77 K are available in the literature, for example, Beebe et al [20,21], Grillet et al [18]. Bobka et al [22], Pace and Siebert [23], and Avgul and Kiselev [19].…”
Section: Isosteric Heatmentioning
confidence: 99%
“…In adsorption from the gaseous phase, information about the heat can be a very valuable supplement to isotherm measurements. Experimentally isosteric heat can be measured either by calorimetric means [1][2][3][4][5][6][7][8][9], or calculated using the Clapeyron equation from isotherms at various temperatures. This only provides us with the overall heat released from the process.…”
Section: Introductionmentioning
confidence: 99%
“…In every case, the isotherms were smooth Type I1 isotherms without any of the humps which have become associated with homogeneous surfaces (1). Hence, it was concluded that these graphites presented heterogeneous surfaces to gases a t liquid nitrogen temperatures.…”
Section: Introductionmentioning
confidence: 81%